ANALYSIS OF ISLAMIC STOCK PRICE INDEXS IN INDONESIA - desi novera danur (Fakultas Syariah dan hukum Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
ABSTRACT This study aims to determine whether there is an effect of macroeconomic indicators on the Indonesian Islamic stock price index (ISSI) as an dependent variable. The macroeconomic indicators tested in this study are inflation, exchange rates, interest rates (interbank rates), gold prices and world oil prices which are independent variables. This study uses monthly time series data from the 2015-2019 period. This type of research is a multiple linear regression Quantity research with the analytical tool used by ARDL to measure the research parameters. The findings of the research show that the inflation and gold price variables have a significant effect on ISSI both in the short and long term, while the other three variables, namely the exchange rate, interest rate and world oil price have an insignificant effect even though the oil price variable the world has a positive relationship, marked by a positive coefficient value. Keywords : Syariah Stock Index, Macroeconomic Variables